How do various strategies for returning residues change microbiota modulation: potential implications for soil health - Jiang, Nan; Chen, Zhenhua; Ren, Yi; Xie, Shichang; Yao, Zimeng; Jiang, Dongqi; Zhang, Yulan; Chen, Lijun (Frontiers in Microbiology, 2025)
IntroductionResidue incorporation is a crucial aspect of anthropogenic land management practices in agricultural fields. However, the effects of various returning strategies on the soil microbiota, which play an essential vital role in maintaining soil health, remains largely unexplored.MethodsIn a study conducted, different residue management strategies were implemented, involving the application of chemical fertilizers and residues that had undergone chopping (SD), composting (SC), and pyrolysis (BC) processes, with conventional fertilization serving as the control (CK).Results and discussionUsing metagenomic sequencing, the analysis revealed that while all residue returning strategies had minimal effects on the diversity (both α and β) of microbiota, they did significantly alter microbial functional genes related to carbon (C), nitrogen (N), phosphorus (P), and sulfur (S) cycling, as well as the presence of antibiotic resistance genes (ARGs) and pathogens. Specifically, chopped residues were found to enhance microbial genes associated with C, N, P, and S cycling, while composted residues primarily stimulated C and S cycling. Furthermore, all residue treatments resulted in a disruption of relationships among nutrient cycles, with varying degrees of impact observed across the different management strategies, with the sequence of impact being SD < SC < BC. Moreover, the residue additions resulted in the accumulation of ARGs, while only SC caused an increase in certain pathogens. Finally, through analyzing the correlation network among indices that exhibited active responses to residue additions, potential indicators for functional changes in response to residue additions were identified. This study further offered recommendations for future cropland management practices aimed at enhancing soil health through microbiomes.